UJI EFEKTIFITAS PENAMBAHAN AIR KELAPA FERMENTASI, ASAM ASETAT, ETANOL, DAN GARAM PADA GLIFOSAT TERHADAP GULMA DI PERKEBUNAN SAWIT YANG BELUM MENGHASILKAN - Nurlianti; Prihanani; Aishar Muhammad Fikri Nur Ikhsan; Risvan Anwar; Eka Suzanna; Farida Aryani (University of Prof. Dr. Hazairin, SH, 2025)
Oil palm is a strategic commodity that plays a vital role in Indonesia's economy, but its productivity is often hindered by weed infestation. Chemical weed control commonly relies on synthetic herbicides, which pose environmental risks. This study aims to evaluate the effectiveness of a new natural-based herbicide formulation consisting of fermented coconut water, ethanol, acetic acid, salt, and low-dose glyphosate in immature oil palm plantations. The research employed a single-factor Randomized Complete Block Design (RCBD) with nine formulation treatments and three replications. Vegetation analysis revealed three dominant weed species in the experimental area: Borreria alata, Ageratum conyzoides, and Asystasia gangetica. The results indicated that all herbicide formulations were able to suppress weed populations and dry weight, although the differences were not statistically significant. Numerically, Formulation 8 (F8) provided the best results, achieving a weed mortality rate of up to 99%. In contrast to previous formulations requiring high application volumes (35–50 L/ha), this new formulation is more efficient at a dosage of 4–6 L/ha. This formulation works synergistically, is environmentally friendly, and has the potential to support sustainable agricultural practices